Sirfídeos predadores (Diptera, Syrphidae) em cultivos orgânicos de couve - Ragi, Alexandra Aparecida Máximo (2017)
Within Diptera, Syrphidae is one of the most diverse families. Most adults are flower visitors, feeding on pollen and nectar. On the other hand, the larvae present a remarkable morphological variety and different feeding habits, being predators, saprophagous, phytophagous and parasitoids. Considering the great potential of the immature predatory Syrphidae as agents in biological pest control and studies about their activities are scarce in Brazil, as well as in the Neotropical region, the identification of these organisms is of utmost importance to draw up strategies of their real applicability. This work aimed to identify immature predatory Syrphidae species in organic cabbage cultivation, with and without maintenance of non-crop vegetation; to verify the diversity and abundance of the species of immature throughout t he phenological phases of cabbage and if the flowering of maintained non-crop vegetation can influence the syrphid diversity and abundance, besides indicating which species of Syrphidae would have a potential to trace further studies to a possible applied use on biological control. For this, weekly collections of immature Syrphidae were carried out in four circular beds, of organic culture of cabbage, two with and two without maintenance of non-crop vegetation, from February to November 2016, totalling 42 samplings. The Shannon‟s diversity indexes were calculated for immature Syrphidae species among the beds and was performed comparison analyses of diversity, richness and abundance averages in relation to the sampled beds were performed. In order to visually and identify differences in species composition of the immature syrphids among the beds the Nonmetric multidimensional scaling was performed. To verify if climatic factors interfered on richness and abundance of the immature Syrphidae, Pearson's correlation was performed. Were collected 2761 immature syrphids, of which eight species were identified, distributed in four genera. Allograpta exotica was the most abundant species, standing out from the other species in most of samplings. From all the evaluations regarding the richness, abundance, diversity and composition of Syrphidae species in the different beds, it was noticed that the maintenance of non-crop vegetation has no correlation with the occurrence of immature syrphids. The temperature on the richness and the temperature on the abundance of Syrphidae species were the most important climatic variables. In addition, a high positive correlation o f the pest level on the abundance of Syrphidae species was observed. Therefore, the high correlation of larvae with the level of the pest leads to the conclusion that as the abundance of adults is directly proportional to the quantity of floral resources, the abundance of larvae is directly proportional to the abundance of their food resources. The results here obtained are a first step to the knowledge of the importance of Syrphidae in pest predation, since many species have a high potential in biological control and little is known due the lack of basic studies on biology and taxonomy.